Evaluasi awal kerentanan pelulukan/likuefaksi daerah Kendal dan sekitarnya, Jawa Tengah - Lumbanbatu, Ungkap M.; Hidayat, Suyatman (Indonesian Journal on Geoscience, 2007)
http://dx.doi.org/10.17014/ijog.vol2no3.20074The investigated area is a region prone to liquefaction hazards since it consists of loose, saturated Quaternary deposits. The Quaternary deposits were deposited in several sediment environments such as swamp, estuary, near shore, off shore, and fluvial (flood plain, flood basin and paleo channel). Among those Quaternary deposits, the paleo channel and estuary deposits which mainly consist of fine - to medium - sand have high susceptibility to liquefaction. An earthquake-source zone which is able to trigger earthquake and to cause liquefaction hazards is known to be thrust fault and subduction zones. Earthquakes produced by thrust fault activities are classified as shallow earthquakes while earthquakes produced by a subduction zone are deep earthquakes. The investigated area is divided into low liquefaction susceptibility, moderate susceptibility and high liquefaction susceptibility zones. This division has been made based on physical characteristic of the sand deposits, grain size, thickness of sand and its position to groundwater level as well as the physical character of overburden layer. Â